الرياضيات بالعربية

تمرين حول دالة الجزء الصحيح

بين الخاصيات التالية :

$(\forall x \in \mathbb{R}) \, (\forall n \in \mathbb{Z}) \, : \quad \text{E}(x + n) = n + \text{E}(x)$

$(\forall x,y \in \mathbb{R}) \, : \quad \text{E}(x) + \text{E}(y) \leq \text{E}(x + y) \leq \text{E}(x) + \text{E}(y) + 1$

$(\forall x \in \mathbb{R}) \, (\forall n \in \mathbb{N}^{*}) \, : \quad 0 \leq \text{E}(n x) - n \text{E}(x) \leq n - 1$
راجع الدرس : دالة الجزء الصحيح


ليكن $n \in \mathbb{Z}$ و $x \in \mathbb{R}$ :

نعلم أن $\text{E}(x) \leq x < \text{E}(x) + 1$

إذن $n + \text{E}(x) \leq x + n < n + \text{E}(x) + 1$

نضع $N = n + \text{E}(x)$

لدينا $N \in \mathbb{Z}$ بحيث $N \leq x + n < N + 1$

إذن $\text{E}(x+n) = N = n + \text{E}(x)$

خلاصة : $(\forall x \in \mathbb{R}) \, (\forall n \in \mathbb{Z}) \, : \quad \text{E}(x + n) = n + \text{E}(x)$


ليكن $x,y \in \mathbb{R}$, لدينا :

$\left\{ \begin{array}{cl}x - 1 < \text{E}(x) \leq x \\y - 1 < \text{E}(y) \leq y\end{array} \right. \implies x + y - 2 < \text{E}(x) + \text{E}(y) \leq x + y$

نضع $N = \text{E}(x) + \text{E}(y)$, لدينا $N \leq x + y$

إذن $N \leq \text{E}(x + y)$

خلاصة $\text{E}(x) + \text{E}(y) \leq \text{E}(x + y)$

ولدينا : $x + y - 2 < N$

إذن $\text{E}(x + y - 2) < N$

وكما بينا سابقا : $\text{E}(x + y - 2) = \text{E}(x + y) - 2$

وبالتالي $\text{E}(x + y) < N + 2$

إذن $\text{E}(x + y) \leq N + 1$ (لأن $N$ و $\text{E}(x + y)$ أعداد صحيحة)

خلاصة $\text{E}(x + y) \leq \text{E}(x) + \text{E}(y)$

$(\forall x,y \in \mathbb{R}) \, : \quad \text{E}(x) + \text{E}(y) \leq \text{E}(x + y) \leq \text{E}(x) + \text{E}(y) + 1$


ليكن $n \in \mathbb{N}^{*}$ و $x \in \mathbb{R}$ :

نعلم ان $n x - 1 < \text{E}(nx) \leq n x$

ونعلم : $x - 1 < \text{E}(x) \leq x$

إذن $-n x \leq -n \text{E}(x) < n - n x$

إذن $ - 1 < \text{E}(n x) - n \text{E}(x) < n$

وبالتالي $0 \leq \text{E}(n x) - n \text{E}(x) \leq n-1$

خلاصة : $(\forall x \in \mathbb{R}) \, (\forall n \in \mathbb{N}^{*}) \, : \quad 0 \leq \text{E}(n x) - n \text{E}(x) \leq n - 1$